“C’è l’Assaorta che ci aspetta...”. Geografi ed etnografi italiani tra i Saho d’Eritrea - Gianni Dore (Ethnorêma, 2009)
At the very beginning of the XX c. four Italian geographers and ethnologists reached Eritrea to do a scientific survey of several Saho groups. Their aim was to collect data on Saho material culture, as well as on their myths of origins, historical accounts, riddles, and genealogies. They sought support for their research insisting that it would also be useful to colonial administrators. This essay takes into account the methodology of their inquiry, the colonial practices and sheds light on the complex and ambiguous relationship between researchers, colonial officers, local chiefs and inhabitants in the Akkälä Guzai region in that early stage of Italian colonial rule. As a product of that mission a rich ethnographic collection of Saho handcrafts reached Florence where it was kept in the Museum of Anthropology and partly exhibited. It is a remarkable resource on the Saho cultural heritage. That old mission and its results are the scientific basis on which today’s field research mission with its own linguistic and ethnographic goals is based.